Optical, magnetic and dielectric properties of non-liquid crystalline elastomers doped with magnetic colloids - Neto, A. M. Figueiredo (2020)
Magnetic nanoparticles from magnetic colloidal suspensions were incorporated in the urethane/urea elastomer (PU/PBDO) by swelling fully crosslinked elastomer samples with a toluene and ferrofluid mixture. It is shown that ferrofluid grains can be efficiently incorporated into the matrix of elastomers. The dependence of the birefringence of both the pure and ferrofluid-doped elastomer samples on strain is linear. The ratio of birefringence to strain of the ferrofluid-doped samples is greater than that of the pure elastomer samples, indicating that ferrofluid grains are oriented by the strained polymer network. We propose that this strain-induced orientation is due to the shape anisotropy of the nanoparticles.